Tensions in the management of the Benefit of Continued Provision at School Program - Reginaldo Célio Sobrinho; Monica Isabel Carleti Cunha; Edson Pantaleão (Arizona State University, 2018)
The "Benefit of Continued Provision Continued at School" Program is intersectoral and aims to identify and act in overcoming barriers that prevent the effectiveness of the schooling process of children and adolescents with disabilities in situations of extreme poverty. The coordination of this program takes place through management groups, legally constituted in the states and in the municipalities. Considering the relevance of this program in the set of actions that induce public policies, in this text we aim to problematize questions related to the composition and work dynamics of the Local Management Committee of the "Benefit of Continued Provision Continued at School" Program, which operates in the city of Vitória-ES. The collection and production of the data was guided by the theoretical-methodological perspective of Figurational Sociology, elaborated by Norbert Elias. We studied documents, conducted semi-structured interviews involving the members of the Management Committee and accessed the "memories" of six regular meetings held by that committee in the year 2015. From the results, we observe that neoliberal policies underway bring immediate implications to the activities of the Local Management Committee. Associated with this, we observed that the significant turnover of its members causes difficulties and impasses in political and administrative referrals. It is important to emphasize the pertinence of the municipal administration to commit themselves to a work agenda that guarantees planning, execution and evaluation of the social policies implemented.